Sequential kraft lignin fractionation for nanoparticle production: the use of green solvent approach - Rodrigues, Jéssica de Souza (2025)
In the context of biorefineries, kraft lignin (KL) has emerged as an underexplored yet promising resource. Its phenolic structures are crucial, offering a wide range of applications, from advanced materials to nanotechnology. This study investigates the sequential fractionation of KL in acetic acid (HOAc), a green solvent, to produce lignin nanoparticles (LNP). KL fractions were obtained at HOAc concentrations ranging from 10 % to 60 %. The most promising fractions, namely KL_30%, KL_40%, KL_50%, and the final residue (FR), were selected based on high extraction yield and distinct molar masses (Mw) for LNP preparation using the antisolvent precipitation method. The study explores the influence of Mw, chemical composition, and functionality of LNPs on their properties. The results demonstrated an inverse correlation between Mw and the hydrodynamic diameter of LNPs, where lower Mw fractions (KL_30% and KL_40%) resulted in larger particle sizes, while KL_50%, despite its higher Mw, produced the smallest LNPs. This finding reinforces the idea that Mw alone does not dictate particle size, and the chemical functionality of lignin - particularly the balance between phenolic and aliphatic groups - plays a crucial role in determining aggregation behavior, surface charge, and colloidal stability. A deeper understanding of these structure-function relationships opens new opportunities for optimizing lignin fractionation and tailoring LNPs for specific applications in nanotechnology and advanced materials.